2019
DOI: 10.17712/nsj.2019.2.20180037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smartphone overuse on headache, sleep and quality of life in migraine patients

Abstract: Objectives: To investigate the effects of smartphone overuse on headache, sleep quality, daytime sleepiness and quality of life in migraine patients. Methods: This study is a single-center, cross sectional comparative study. This study was conducted between July and September 2017 in the Neurology Clinic of a private hospital. Migraine disability assessment)MIDAS(questionnaire was used to evaluate the disability status, and Mobile Phone Problematic Use Scale)MPPUS(was used to evaluate smartphone use frequency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 29 publications
4
41
3
2
Order By: Relevance
“…Higher scores on both smartphone addiction scales were shown by evening oriented students. These studies concluded that the smartphone addiction is affecting students' lives by developing significant sleep and behavior problems [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores on both smartphone addiction scales were shown by evening oriented students. These studies concluded that the smartphone addiction is affecting students' lives by developing significant sleep and behavior problems [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study illustrates that Smartphone overuse has been examined to poor sleep quality and daytime sleepiness. Moreover, increase/elevation in the smartphone usage, provoke daytime sleepiness, reduces the sleep quality, and quality of life is reduced as well [31].…”
Section: Sleep Patternmentioning
confidence: 99%
“…Excessive mobile phone use correlated with disturbed sleep pattern and quality (70) Excessive smartphone use was associated with poorer sleep quality and higher perceived stress (71,72), lowered physical activity, lower muscle mass and higher fat mass (73). Other medical conditions include acquired comitant esotropia (AACE) (74) increased ocular symptoms (75), headache complaints (76,77) and headache duration and frequency in migraine patients (78). Young chronic neck pain patients with overuse of smartphones had higher Cervical Disc Degeneration (79).…”
Section: Medical Complications-sleep Physical Fitness Eyesight Migraine and Painmentioning
confidence: 99%
“…A large epidemiological study (involving 1,501,914 subjects) showed that 63% of adolescents (11-15 years of age) use mobile phones and, among them, 23% suffered from migraine, and 5% suffer from insomnia (that is known as strictly connected to migraine) (75). In a single-center, cross-sectional study involving a total of 123 patients, Demir and Sumer observed that the use of smartphones increases headache duration and frequency of migraine among adult patients due to ensuing poor sleep quality and daytime sleepiness (76).…”
Section: Technology and Headachementioning
confidence: 99%